2019
DOI: 10.7150/jca.35465
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Age-adjusted Charlson comorbidity index on the short- and long-term outcomes of patients undergoing curative gastrectomy for gastric cancer

Abstract: Background: The aim of this study was to determine whether or not the short- and long-term outcomes were affected by the age-adjusted Charlson comorbidity index (ACCI) in patients who underwent curative resection for gastric cancer.Methods: The patients were retrospectively selected from among the medical records of consecutive patients who underwent curative gastrectomy with nodal dissection for gastric cancer at Yokohama City University and Kanagawa Cancer Center from January 2000 to August 2015.Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
3
31
0
2
Order By: Relevance
“…The relationship between increased prevalence of comorbidities and deleterious outcome in cancer patients has been analyzed in various tumor entities [ 19 , 20 ]. For cutaneous malignant melanoma, a comprehensive cancer registry-based study on a Danish population revealed more advanced tumor stages to be prevalent in patients with increased comorbidity levels [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between increased prevalence of comorbidities and deleterious outcome in cancer patients has been analyzed in various tumor entities [ 19 , 20 ]. For cutaneous malignant melanoma, a comprehensive cancer registry-based study on a Danish population revealed more advanced tumor stages to be prevalent in patients with increased comorbidity levels [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have described the relationship between ACCI and survival for gastrointestinal cancer patients. Maezawa et al investigated the survival impacts of ACCI in 2254 patients who received radical gastrectomy for gastric cancer (17). They divided the patients into two groups: low-ACCI group (n=1656) and high-ACCI group (n=598).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously explored the appropriate cut-off value of ACCI in several cancers. In the gastrointestinal region, Lin et al set 3 as the cut-off value in 1476 gastric cancer patients, and Maezawa et al set 6 as the cut-off value in 2254 gastric cancer patients (17,18). In the hepato-biliary pancreatic cancer region, Qu et al set 4 as the cut-off value in 268 intrahepatic cholangiocarcinoma patients, and Takahara et al set 5 as the cut-off value in biliary tract cancer (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that some post-ESD elderly patients can benefit from additional treatment. Several studies have clarified the relationship between CCI and complications of elderly gastric patients after ESD, which showed CCI can serve as an independent prognostic factor (12,(19)(20)(21), and the significance of CCI in patients with non-curative EGAC after ESD remained unclear. Our study demonstrated that age and higher CCI score (≥2) were independent prognostic factors in elderly patients with EGAC treated using ESD, similar to the findings reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%